2017
DOI: 10.1039/c7ra01934c
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring surfactant mediated defence of gastrointestinal Proteus mirabilis DMTMMK1 against pathogenic consortia of Vibrio cholerae

Abstract: Schematic representation of the biosurfactant production and evaluation of anti-pathogenic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…The biofilm image analysis portrayed the reduction in biofilm formation and disruption of preformed biofilms in the presence of biosurfactant. The biosurfactant treatment in the preformed biofilms of V. harveyi efficiently crumbled the biofilm architecture when compared with the untreated control as portrayed in V. cholerae . The outcome we perceived here is comparable to what has been stated before for V. harveyi and V. parahaemolyticus with the treatment of ethanolic extract of the red seaweed Gracilaria fisheri .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The biofilm image analysis portrayed the reduction in biofilm formation and disruption of preformed biofilms in the presence of biosurfactant. The biosurfactant treatment in the preformed biofilms of V. harveyi efficiently crumbled the biofilm architecture when compared with the untreated control as portrayed in V. cholerae . The outcome we perceived here is comparable to what has been stated before for V. harveyi and V. parahaemolyticus with the treatment of ethanolic extract of the red seaweed Gracilaria fisheri .…”
Section: Discussionsupporting
confidence: 80%
“…The disintegrated biofilm architecture reveals the effectiveness of biosurfactant, which is due to the disturbance in interbacterial adhesion facilitated by the negative charge of the MK3 biosurfactant. The cell surface morphology confers a selective advantage toward bacterial virulence by aiding the process of adhesion toward the host cell and evasion against immune system . In this study, we demonstrated that the biosurfactant could damage the cell wall and were able to destroy the entire cell structure, this would provide a more effective strategy of the biosurfactant to treat against V. harveyi .…”
Section: Discussionmentioning
confidence: 76%
“…The surfactant activity was quantitatively evaluated by the emulsification index (EI 24 ) and surface tension determination. For the molecular identification of the best biosurfactant producer strain, the 16S rRNA region was amplified using the universal primers 27F/1492R 30 . PCR products were purified and sequenced.…”
Section: Methodsmentioning
confidence: 99%
“…Culture conditions and biosurfactant preparation were carried out as described by Kannan et al . 30 . Acid precipitated biosurfactant was subjected to repeated extractions with an ethyl acetate–methanol mixture (2:1, v/v).…”
Section: Methodsmentioning
confidence: 99%
“…After adding 2 mL of 0.85% saline to the collection tubes, the rectal swab samples were vortexed for 10 min at room temperature and allowed to stand for 5 min, according to a previously reported protocol with minor modifications [17] . Next, 10 μL supernatant was taken and inoculated on MacConkey agar (Difco Laboratories, Detroit, MI, USA) for overnight culturing at 37ºC.…”
Section: Isolation and Identification Of E Coli Strainsmentioning
confidence: 99%